Influence of inclusion of grapevine leaves, rachis and peduncles during fermentation on the flavour and volatile composition of Vitis vinifera cv. Shiraz wine. (5th April 2021) - Capone, D.L.; Barker, A.; Pearson, W.; Francis, I.L.
Abstract: Background and Aims: The presence of matter other than grapes (MOG) is common in the winemaking process when sorting equipment is not utilised. Experimental wines were made to examine the effect of MOG on the sensory profile and chemical composition of wine. Methods and Results: A Shiraz wine made without MOG was compared to fermentations with grape leaves, grape stalks (rachis) and peduncles (the stalk connecting the bunch to the vine) added at amounts at or slightly above those found in a commercial harvest bin. Fifty‐one volatile aroma compounds were quantified in the wines, and sensory descriptive analysis was applied. The wine made with leaves added was rated by the sensory panel similar to the Control and was significantly higher only in positive aromas such as 'confectionery' and 'red fruit' likely due to a higher concentration of hexanol and ( Z )‐3‐hexen‐1‐ol. The addition of peduncles slightly enhanced 'green' aroma and flavour. The rachis treatment was high in 'green capsicum/green stalks' attributes, as well as astringency, and was high in methoxypyrazines. Conclusions: The inclusion of different types of MOG during fermentation can alter the sensory profile and chemical composition of Shiraz wines in varying ways, including extraction of methoxypyrazines from the rachis, resulting in notable 'green' attributes. Significance of the Study: The inclusion of MOG is unavoidable in common winemaking practices, especially with the use of mechanical harvesting. Determining the influence of MOG on the volatile composition of the finished wine is an important step in manipulating wine style.